Calculation and Analysis of Mesh Stiffness of Spur Gear based on LTCA - Zhengjiu Feng; Guanghu Jin; Rupeng Zhu (Jixie chuandong)
Using Matlab software and three-dimensional finite element method, the flexibility matrix of spur gear tooth surface is obtained, and three calculation methods of matrix are compared and analyzed. The mesh stiffness of spur gear pair is obtained by establishing two kinds of loaded tooth contact analysis (LTCA) models, including line-contact and face-contact model. The effects of wheel flange thickness, web thickness,applied load and different contact models on mesh stiffness are analyzed.The results show that the mesh stiffness difference obtained by two kinds of contact model is small. When the flange thickness is small, the meshing stiffness is greatly affected while the web thickness has little effect on the mesh stiffness. In the given example, the influence of flange thickness on meshing stiffness tends to be gentle when the ratio of flange thickness to modulus is more than 3.5.